PERBANDINGAN TINGKAT KEBUGARAN JASMANI ANTARA SISWA KELAS KHUSUS DAN KELAS REGULER (STUDI PADA SISWA KELAS X SMA AL-ISLAM KRIAN TAHUN AJARAN 2012-2013) - KRISDIAWAN, DHAFID (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract One of the objectives of physical education, sport, and health is to improve the physical fitness of students. Physical fitness has the meaning of someone’s physical ability to perform daily corporality tasks optimally even he is still able to do physical activities without incurring additional significant fatigue. Learning physical education, sport, and health at SMA Al-Islam Krian was done in all classes. The lesson schedule for regular class is from 6:45 to 15:30 WIB on Monday up to Wednesday. While the lesson schedule for regular class is from 6:45 to 13:45 WIB on Monday up to Friday, while on Saturday the lesson schedule is from 6:45 to 9:45 WIB. The purposes of this study are: 1. To find the differences of physical fitness grade between regular and special classes in class X SMA Al-Islam Krian. 2. To find out which physical fitness grade between regular and special classes in class X SMA Al-Islam Krian is better. The population of this study is the students of class X SMA Al-Islam Krian which consists of 12 regular classes and the number of each class is 35 students, so the number of all classes is 420 students. As for the special class consists of 3 classes and the number of each class is  35 students, so the number of all classes is 105 students. Large population is 525 students. Sampling technique uses Cluster Random Sampling and it can be taken from 2 classes 1 class is taken from regular class and 1 class is taken from special class. The research type uses comparative research. The Instrument in this study uses TKJI, with data analysis uses the Mann Whitney test. Based on the TKJI test results in class X SMA Al-Islam Krian in a special class with the number of students is 29, with an average score of 12,72, and a standard deviation of 1,907. While regular classes with the number of students is 32, with an average score of 13,16, and a standard deviation of 1,743. Based on the results of data analysis uses the Mann-Whitney Test showed that Ho accepted and Ha rejected because sig (0,026) <alpha of 0,05. So there is no significant difference of physical fitness grade between regular and special classes, but when it is seen from the average value, regular class has an average value greater than the special class, with an average difference of 0,44. Keywords: physical fitness level, special class and regular class students.